The finance-investment link in a transition economy: Evidence for Poland from panel data - Christian E. Weller (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
Real investment in Poland declined from 1990 to 1993, and only slowly recovered, while real credit decreased for a number of years, too. Has declining credit adversely affected investment? Controlling for industry and time fixed effect, and using dynamic panel data techniques, I estimate an investment model, which includes external and internal finance as investment determinants. The results suggest that internal and external finance are positively related to investment. Thus, industries seems to operate under hard budget constraints. Also, internal finance is more important than external finance in determining investment, thus indicating that credit rationing occurs. Finally, the effects of external finance are slightly larger among durable goods producing industries than in non-durable goods producing industries.
Keywords: E22; F36; O16; 330